Pharmacological Properties and Standardization of Ngoc Linh Ginseng using Ultrasonic-Assisted Extraction - Nguyễn Ngọc Mai Thảo; Trung Phung-Van; Nguyen Tan Thuong (Journal of Advances in Medicine and Pharmaceutical Sciences, 2025)
This study aims to evaluate the pharmacological potential and standardize the bioactive compounds of Ngoc Linh Ginseng (Panax vietnamensis) as a candidate phytopharmaceutical. The study was conducted throughout 2024 using a multidisciplinary approach, including ultrasonic extraction, chemical analysis, and pharmacological tests. Samples were collected from the Kon Tum and Quang Nam mountains, Vietnam, then extracted by the Ultrasonic-Assisted Extraction (UAE) method using ethanol-water solvents. The total saponin content obtained was analyzed using High Performance Liquid Chromatography (HPLC), resulting in a level of 28.5% with the identification of the main ginsenosides Rg1 and Re. Pharmacological activity was tested in vitro on LPS-induced RAW 264.7 cells, showing a decrease in pro-inflammatory cytokine production by up to 50% and strong antioxidant activity with an IC50 value of 25 µg/mL. In vivo tests on Wistar rats showed a hepatoprotective effect against liver damage caused by a high-fat diet. These results support the potential of Ngoc Linh Ginseng as a candidate for plant-based therapy. Further studies are recommended to explore the pharmacokinetics, clinical efficacy, and optimization of extraction techniques to expand its therapeutic applications.